2013
DOI: 10.1007/s11250-013-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification by culture, PCR, and immunohistochemistry of mycoplasmas and their molecular typing in sheep and lamb lungs with pneumonia in Eastern Turkey

Abstract: This study used cultures, polymerase chain reaction (PCR), and immunoperoxidase to examine samples from 216 lungs from sheep and lambs with macroscopic pneumonia lesions for the presence of Mycoplasma species. DNA was extracted from lung tissue samples and broth cultures with the help of a DNA extraction kit and replicated using genus-specific and species-specific primers for mycoplasma. The lung samples were examined by the immunoperoxidase method using hyperimmune Mycoplasma ovipneumoniae serum. The randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
2
5
0
2
Order By: Relevance
“…Ackermann and Brogden (2) state that the brochus, bronchulus, alveoli and glands perform many tasks, such as antimicrobial activity, inflammatory response and detoxification of toxins. In previous studies, Mannheimia, Pasteurella and Mycoplasma agents were most commonly detected by immunohistochemical examinations in bronchial, bronchiolar, alveolar, epithelial and inflammatory cells (3,8,16,24,27,30). In this study, the expression of COX-2, HMGB-1 and CD68 was found in the above-mentioned structures by immunohistochemical analysis.…”
Section: B High Magnification Of Immunopositive Macrophages In Peribsupporting
confidence: 58%
“…Ackermann and Brogden (2) state that the brochus, bronchulus, alveoli and glands perform many tasks, such as antimicrobial activity, inflammatory response and detoxification of toxins. In previous studies, Mannheimia, Pasteurella and Mycoplasma agents were most commonly detected by immunohistochemical examinations in bronchial, bronchiolar, alveolar, epithelial and inflammatory cells (3,8,16,24,27,30). In this study, the expression of COX-2, HMGB-1 and CD68 was found in the above-mentioned structures by immunohistochemical analysis.…”
Section: B High Magnification Of Immunopositive Macrophages In Peribsupporting
confidence: 58%
“…The rate of detection of Mycoplasma directly from the lungs as per PCR results (87.8%) was higher than the detection rate via culturing technique, suggesting that the detection and diagnosis of Mycoplasma species may be carried out directly from the tissues, especially lungs, without the need for culturing techniques, which take at least 14 days, thus reducing the time needed for the diagnosis of Mycoplasma infections 16,20,22 . The current study used sulphadimidinetrimethoprim plus nystatin for the first time instead of thallous acetate as an inhibitor for the growth of gram-negative bacteria and fungi, and it provided excellent results for isolation without contamination.…”
Section: Discussionmentioning
confidence: 97%
“…DNA extraction was performed from both, lung tissue and Mycoplasma colonies (19)(20)(21)(22). Mycoplasma genomic DNA was extracted from lung tissue and Mycoplasma colonies using the gSYNC™ Geneaid kit (Korea) following the manufacturer's instructions.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Süt örneklerinin bakteriyolojik ve Ma spesifik PCR ile incelenmesi neticesinde %81.7'sinde M. agalactiae saptamışlardır [13] . Özdemir ve Türkaslan [14] ise yaptıkları çalışmada, Bulaşıcı Agalaksi'den şüpheli 22 [10,[20][21][22] . Türkiye'de Bulaşıcı Agalaksi hastalığına yöne-lik spesifik çalışma sayısı çok az olmakla birlikte mevcut çalışmalar ile karşılaştırıldığında çalışmamızdaki etken izolasyon oranının düşük olduğu görülmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…Türkiye'de mikoplazmaların enfekte hayvanlardan izolasyonu ile ilgili birçok çalışma mevcut olmasına rağmen [8][9][10][11][12] , Bulaşıcı Agalaksi Hastalığı üzerindeki çalışma sayısı sınır-lıdır [13][14][15] . Çetinkaya ve ark.…”
Section: Introductionunclassified